2011
DOI: 10.9735/0975-4423.3.2.88-99
|View full text |Cite
|
Sign up to set email alerts
|

L-Asparaginase-an Anti Tumor Agent Production by Fusarium Equiseti Using Solid State Fermentation

Abstract: L-asparaginase (L-asparagine amido hydrolase, E.C.3.5.1.1) is a promising chemotherapeutic agent which plays a vital role in treatment of a variety of lymphoproliferative disorders, lymphosarcoma and acute lymphoblastic leukemia in particular. An attempt is made in the present study to optimize the production of L-asparaginase by Fusarium equiseti using soya bean meal under solid state fermentation (SSF). The maximum yield of L-asparaginase (8.51 IU) was achieved with the following optimized fermentation param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Sucrose and fructose also supported l -asparaginase production to a significant degree but glucose acted as good inducer and primary source of carbon for biosynthesis of l -asparaginase using C 7 . Several reports suggest that glucose serves as a best carbon source for l -asparaginase production and a similar effect was observed for l -asparaginase production using Aspergillus and Fusarium strains (Baskar and Renganathan 2012; Hosamani and Kaliwal 2011). Effect of nitrogen compounds on l -asparaginase by C 7 was studied by supplementing nitrogen sources (asparagine, yeast extract, peptone and sodium nitrate) to MCD medium.…”
Section: Resultsmentioning
confidence: 53%
“…Sucrose and fructose also supported l -asparaginase production to a significant degree but glucose acted as good inducer and primary source of carbon for biosynthesis of l -asparaginase using C 7 . Several reports suggest that glucose serves as a best carbon source for l -asparaginase production and a similar effect was observed for l -asparaginase production using Aspergillus and Fusarium strains (Baskar and Renganathan 2012; Hosamani and Kaliwal 2011). Effect of nitrogen compounds on l -asparaginase by C 7 was studied by supplementing nitrogen sources (asparagine, yeast extract, peptone and sodium nitrate) to MCD medium.…”
Section: Resultsmentioning
confidence: 53%
“…1 ). Previous studies have shown that a nitrogen source is the limiting factor and plays key role in the L-asparaginase production [29]. It seems that L-asparagine might be an inducer for L-asparaginase production and hence the production of the enzyme is more feasible at the presence of this nitrogen source compared to L-arginine and NaNO 3 + (NH 4 ) 2 SO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…3a, 10% moisture is insufficient for enzyme production, while at higher levels of moisture content, the enzyme activity was reduced. In SSF using agricultural residues, the optimum moisture content for L-asparaginase production by non-endophytic fungi lies in the range of 50-70% [9][10][11] . Reduction in L-asparaginase activity at low moisture level has also been reported in case of Penicillium sp.…”
Section: Solid-state Fermentation Using Puf: Effect Of Process Paramementioning
confidence: 99%
“…Reduction in L-asparaginase activity at low moisture level has also been reported in case of Penicillium sp. under SSF with sugarcane bagasse 9 . The amount of moisture content has to be appropriately chosen to permit accessibility to the nutrients in the media.…”
Section: Solid-state Fermentation Using Puf: Effect Of Process Paramementioning
confidence: 99%
See 1 more Smart Citation